The Influence of Brand Image and Message in Makeup Tutorial Videos on Cosmetic Purchase Decisions - Deavvy M.R.Y Johassan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
One of the sources of cosmetic product information that is easily accessible to consumers is the Youtube video-sharing website. Through Youtube, consumers can find information about cosmetic products through makeup tutorial videos made by beauty teachers. This research discusses the scope of communication in the field of marketing. Using social learning theory, researchers discuss brand image, communication messages, and purchase decisions. The brand image consists of three dimensions, namely favorability of brand association, strength of brand association, and uniqueness of brand association. Communication messages consist of two dimensions, namely verbal messages and non-verbal messages. Meanwhile, the purchase decision consists of five dimensions, namely need recognition, information search, alternative evaluation, purchase decision, and post-purchase behavior. The object in this study is a female population of DKI Jakarta aged 20 – 34 years. Based on the data processing carried out, the research results obtained the influence of brand image on cosmetic purchase decisions by 43.7% and the influence of messages in makeup tutorial videos on Youtube on cosmetic purchase decisions by 29.8%. Meanwhile, the brand image and the message in the makeup tutorial video on Youtube together can influence the decision to buy cosmetics by 50%. This study led to the conclusion that the brand image and message in makeup tutorial videos on Youtube can partially influence the decision to buy cosmetics significantly. In addition to the brand image and the message in the video tutorial makeup, simultaneously on Youtube can significantly influence the decision to buy cosmetics.